Informal learning at work : triggers, antecedents, and consequences - Messmann, Gerhard; Segers, Mien; Dochy, F. J. R. C. (New perspectives on learning and instruction., 2018)
"Informal Learning at Work reflects the growing interest in changing the way the workplace encourages and enhances learning and professional development. Due to societal, economic, and technological developments, organisations face the pressure of growing knowledge-intensity and the need for innovations. As a result, employees are expected to adapt to new situations and constantly update their skillsets within an increasingly challenging environment. This book brings together cross-disciplinary perspectives from leading international researchers, drawing on a range of theoretical and empirical studies.Extensively researched and expertly edited, this new addition to the EARLI New Perspectives on Learning and Instruction series outlines the starting points for future research, and highlights the benefits and implications for those aiming to foster informal learning at work, covering areas such as:professional judgementimproving the structure of work tasksfacilitating innovative work behaviour the place of informal learning within teaching Informal Learning at Work presents original quantitative and qualitative studies as well as integrative analyses of worldwide research and is an invaluable introduction to this highly topical subject."- Resumé vydavatel